The Effect of Heat Application on Fluoride Release in Antibacterial Added Glass Ionomer Cement - Ayça Kurt; Tamer Tüzüner; İlkay Altıntepe; Sema Aydınoğlu; Münevver Sökmen (Cumhuriyet University, 2019)
Objectives: This study aimed to evaluate the effect of heating on the fluoride releasing of glass ionomer cement (GIC) combined with 5% CPC (experimental) or not (control). Materials and Methods: Twenty (n=5; each group) GIC samples were prepared with or without 5% CPC powder. The samples were prepared as non-heating (NH) (n=10) or by heating (H) for 60s (H) (n=10) with a Light Emitting Diode. Flouride releasing pattern was obtained at days 1, 7, 15 and 30. Repeated measurements of two-way ANOVA and Fisher's LSD test was used for comparisons (p<0.05).Results: Interaction (groups x heating x time) effects were obtained (p<0.001). There was no significant difference in fluoride release from the NH control and experimental groups on days 1, 7 and 15, but there was a significant release  in the experimental group at 30 days (p = 0.01). Significantly higher values were obtained in H procedures at days 1 (p=0.026), 7 (p=0.001), 15 (p=0.005) and 30 (p=0.028) for control group compared to the experimental. Significantly increased values were obtained from days 1 up to 30 in NH and H procedures for both groups (p<0.001). Conclusions: Heating of both control and experimental groups showed increased fluoride releasing pattern. The fluoride releasing of 60s heating of GIC containing 5% CPC could have acceptable increased values up to 30 days. The increased fluoride releasing pattern after heating procedure seems to be promising for antibacterial GIC combinations.